Architecting a Janus biomass carbon/sponge evaporator with salt-rejection and ease of floatation for sustainable solar-driven desalination. Issue 5 (26th March 2021) - Xu, Keyuan; Wang, Chengbing; Li, Zhengtong; Yan, Xinyue; Mu, Xueyang; Ma, Miaomaio; Zhang, Pengkui
Abstract : A Janus biomass carbon/sponge (JBCS) solar-driven desalination system is composed of carbonized original leaf particles and commercial melamine sponge seamlessly integrated with each other by a simple "soak-dip" method. Abstract : Solar generation technology is considered to be one of the most promising seawater desalination methods. To achieve a high and stable water production rate, the absorber structure and salt deposition are two key problems to be solved. As an effective salt-rejecting structure, a Janus structure can promote steam generation efficiency by reducing heat loss compared with traditional superhydrophilic structures. Here, we designed a Janus biomass carbon/sponge (JBCS) evaporator composed of carbonized original leaf particles and commercial melamine sponge seamlessly integrated with each other by a simple "soak-dip" method. The upper hydrophobic carbon sponge provides excellent salt-rejection and good heat-localization, while the seamless hydrophilic melamine sponge underneath ensures a continuous water supply. The synergistic advantages of the Janus structure allow the evaporator to maintain a stable photothermal conversion efficiency of 86.5% without salt deposition in 3.5 wt% NaCl solution under 1 sun. Therefore, the sustainable JBCS can be used as a promising option to obtain clean fresh water resources to meet the needs of water-scarce areas.